Transitions Study of predictors of illness progression in young people with mental ill health: study methodology. Issue 1 (24th July 2013) - Purcell, R.; Jorm, A.F.; Hickie, I.B.; Yung, A.R.; Pantelis, C.; Amminger, G.P.; Glozier, N.; Killackey, E.; Phillips, L.; Wood, S.J.; Mackinnon, A.; Scott, E.; et al.
Abstract: Aim: An estimated 75% of mental disorders begin before the age of 24 and approximately 25% of 13–24‐year‐olds are affected by mental disorders at any one time. To better understand and ideally prevent the onset of post‐pubertal mental disorders, a clinical staging model has been proposed that provides a longitudinal perspective of illness development. This heuristic model takes account of the differential effects of both genetic and environmental risk factors, as well as markers relevant to the stage of illness, course or prognosis. The aim of the Transitions Study is to test empirically the assumptions that underpin the clinical staging model. Additionally, it will permit investigation of a range of psychological, social and genetic markers in terms of their capacity to define current clinical stage or predict transition from less severe or enduring to more severe and persistent stages of mental disorder. Method: This paper describes the study methodology, which involves a longitudinal cohort design implemented within four headspace youth mental health services in Australia. Participants are young people aged 12–25 years who have sought help at headspace and consented to complete a comprehensive assessment of clinical state and psychosocial risk factors. A total of 802 young people (66% female) completed baseline assessments. Annual follow‐up assessments have commenced. Conclusions: The results of this study may have implications for the way mental disorders are diagnosed and treated, and progress our understanding of the pathophysiologies of complex mental disorders by identifying genetic or psychosocial markers of illness stage or progression.